The Relationship between the Role of Nurse Educator and Compliance with Control of Pulmonary Tuberculosis Patients at the Pulmonary Polyclinic, Medika Mulia Hospital, Tuban - Miftahul Munir; Nurus Safaah (Alliance oh Health Activists (AloHA), 2020)
Compliance with control of pulmonary tuberculosis patients to the pulmonary clinic is influenced by several factors, one of which is the hospital environment (doctors, nurses, midwives and other health teams). Nurses are professions that are very close to patients, one of the approaches used by nurses is the role of nurses as educators. The purpose of this study was to identify the compliance of Tuberculosis patients for re-control and to find out the relationship between the role of the Nurse Educator and the compliance of control of pulmonary tuberculosis patients to the Tuban Medika Mulia Hospital. The method used in this research is correlation analytic method with cross sectional research design. The population in this study involved 66 pulmonary TB patients in the pulmonary polyclinic of Medika Mulia Tuban Hospital, with the determination of the sample using a systematic random sampling method. Data was collected by using a questionnaire using rho sperm test data analysis. From the analysis results obtained data with a significance value of 0.003 (p